2022
DOI: 10.3390/plants11141853
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Improves Growth and Physiological Attributes and Salt Tolerance Differentially in Two Bread Wheat Cultivars

Abstract: Abiotic constraints such as salinity stress reduce cereal production. Salicylic acid is an elicitor of abiotic stress tolerance in plants. The aim of this study was to investigate the effects of salicylic acid on two bread wheat cultivars (SST806 and PAN3497) grown under salt stress (100 and 200 mM NaCl) in the presence and absence of 0.5 mM salicylic acid. The highest salt concentration (200 mM), in both PAN3497 and SST806, increased the days to germination and reduced the coleoptile and radicle dry weights. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…SA treatments have been shown to enhance grain yield in crops facing heightened stress conditions [ 88 , 89 ]. However, to understand SA’s effects on reproduction under optimal growth conditions, we need to investigate the consequences of SA deficiency on plant growth and reproduction.…”
Section: Hormones With Reduced Reproduction Trade-off Ratiosmentioning
confidence: 99%
See 3 more Smart Citations
“…SA treatments have been shown to enhance grain yield in crops facing heightened stress conditions [ 88 , 89 ]. However, to understand SA’s effects on reproduction under optimal growth conditions, we need to investigate the consequences of SA deficiency on plant growth and reproduction.…”
Section: Hormones With Reduced Reproduction Trade-off Ratiosmentioning
confidence: 99%
“…The positive effects of SA on reproduction assurance are linked to its role in stress tolerance. The treatment of stressed plants with SA has been shown to enhance their ability to withstand stress, thereby ensuring a certain level of reproduction [ 88 , 89 , 93 ]. Notably, SA plays a crucial role in promoting tolerance to various abiotic stresses, including drought, salt, osmotic, and temperature stresses [ 88 , 89 ].…”
Section: Hormones With Reduced Reproduction Trade-off Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…Several physiological and biochemical alterations are induced by drought, causing plants to have many adaptation strategies as defensive survival mechanisms against drought stress. It was reported that different strategies could be followed to reduce food production decreases due to drought in the future [ 8 , 9 ]. The development of drought tolerance mechanisms in food crops is one such strategy.…”
Section: Introductionmentioning
confidence: 99%